the Study on the Functionalization Role of Student Parents in Education Activities - Aloysius Mering (JETL (Journal of Education, Teaching and Learning), 2019)
This study aims to examine and describe the school's efforts to function the role of students parents in the education process at school. Descriptive research methods are used to achieve the research objectives. The study sample was parents and teachers who were purposively determined on the basis of considering the status of school accreditation. The schools selected as samples were Santun Untan Senior High School (accredited B) and Gembala Baik Senior High School (accreditation A). The research data was collected by interview instruments, questionnaires, and documentation. Data analysis was carried out by descriptive statistical studies to describe the optimal functioning of parents by schools. From the research data obtained the fact that the perceptions of parents of students and teachers in Santun Untan Senior High School and Gembala Baik Senior High School toward the relationship between parents and teachers  are "good." In playing the functions of parents in school, both parents and teachers state "no difficulties." Aspects that are considered "important" to "very important" in fostering parent and teacher relationships include not giving up children's affairs to schools, assuming parents as school partners, parents controlling children's education, parents always following the development of the school , and care about children's education. With this perception, it is possible to "ideal conditions" in building optimal cooperation in student education in the two sample schools.